Scientific substantiation of approaches to organization and conducting radiation surveys at the rehabilitated radiation sites - I. K. Romanovich (Радиационная гигиена)
The article is concerned with the scientific justification of approaches to the organization of the final radiation survey of facilities having radioactive contamination, after their rehabilitation. Scientific publications on the previous experience in rehabilitation of facilities contaminated with radionuclides, the organization and conducting a radiation survey before the start of the decontamination, during its implementation and after its completion were analyzed. The experience in the rehabilitation of the site for the temporary storage of spent fuel and radioactive waste in Andreeva Bay in the North-West region of Russia, the locations of peaceful nuclear explosions, experimental nuclear power plants, a radiochemical laboratory, and metallurgical plants, that do not belong to radiation facilities, has been studied. It has been established that, besides the surface contamination of the soil, areas of radioactive contamination on sites of decommissioned radiation facilities with significant depth up to 15 m along the profile are available. These local zones with depth soil contamination are persistent contaminants of the groundwater. The experience in the radiation survey of the peaceful nuclear explosions sites shows the removal of radionuclides from cavities, formed with the use of nuclear explosive technologies for peaceful purposes, on the earth’s surface. An optimized list of radionuclides to be monitored during the radiological survey of rehabilitated facilities was proposed based on the analysis of the composition of radionuclides detected at radiation sites subjected to decontamination. The optimized list includes 14 radionuclides with the half-lives of more than three years.